The use of dabigatran etexilate in hospitalised patients. Issue 2 (12th March 2012) - Cuesta, I.; Delgado, E.; de Salazar, E. Gómez; Bermejo, T.
Abstract : Background: Dabigatran etexilate (DE) is a new oral anticoagulant. It was included in the hospital's formulary as a restricted-use drug in December 2009. Purpose: To analyse DE use, compliance with the authorised indications and use restrictions, and to quantify the incidence of adverse events. Materials and methods: An observational, prospective, utilisation study was carried out over four months in a general tertiary care hospital. The Pharmacy and Therapeutics Committee approved DE, with prescriptions restricted to the Traumatology and Geriatrics Departments for the primary prevention of thromboembolic events in adults who have undergone elective total hip or knee replacement surgery. Patient treatments were reviewed through the CPOE program as were their lab test results and clinical records. DE indications and posology were examined comparing to the summary of product characteristics and the hospital's use protocol. The standard recommended dose in adults is 220 mg/day for 10 or 28-35 days after total knee or hip replacement respectively. The only difference between the drug specifications and the hospital's protocol is that the latter allows the treatment to be extended to 4-6 weeks after total knee replacement. The incidence of adverse events related to DE was recorded. Results: During the study, 138 patients started DE; 78.99% were women, 6.52% had taken it previously and 97.10% were admitted to the Traumatology Unit. In most patients (89.13%), of whom 73.98% had undergone elective total knee replacement surgery and the remaining 26.02% total hip replacement, DE was prescribed for the licensed indications. Treatment duration accorded with the indications in 82.42% and 78.13% of patients respectively. DE was also used 'off-label' (10.87%), mainly for thromboembolic prophylaxis after hip fracture. Overall, 57.24% of prescriptions stuck to the recommendations. Most commonly reported adverse events were: bleeding in the surgical wound (7.97%) followed by gastrointestinal side effects (4.35%). 15.94% of patients needed transfusion of red blood cell concentrates. Conclusions: The use of dabigatran etexilate was appropriate in most patients, but more studies and close monitoring by the pharmacy are needed to confirm the safety of this drug in common practice.